Nodular skin melanomas and dermatoscopic diagnostic therein - M. V. Zhuchkov; M. A. Tarasova; D. B. Sonin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Aim. The study of dermatoscopic pattern characteristics of nodular melanoma with the use of modified Kittler's pattern analysis. Materials and methods. Clinical and dermatoscopis images of 127 patients with histologically distinctive nodular form of skin melanoma were examined. Nonpolarized dermoscopy of nodular melanoma foci was carried out to patients. Interpretation of obtained dermatoscopic images was performed with the use of pattern analysis modified by Harold Kittler. Main results. The two most important dermatoscopic features of nodular melanoma that distinguish it from other clinical types of this malignant tumor were revealed in our investigation: 1) the prevalence of dermatoscopis images with one pattern (structureless); 2) the prevalence of "grey dots, circles, clods" and "black peripheral dots and clods" as main features of nodular melanoma.